Foreign direct investment in East Asia and Latin America: Is there a People's Republic of China effect? - Busakorn Chantasasawat; K. C. Fung; Hitomi Iizaka; Alan Siu (Asian Development Bank Institute (ADBI), 2004)
People's Republic of China (PRC) in recent years has emerged as the largest recipient of foreign direct investment (FDI) in the world. Many analysts and government officials in the developing world have increasingly expressed concerns that they are losing competitiveness to PRC. Is PRC diverting FDI from other developing countries? Theoretically, a growing PRC can add to other countries' direct investment by creating more opportunities for production networking and raising the need for raw materials and resources. At the same time, the extremely low Chinese labor costs may lure multinationals away from sites in other developing countries when the foreign corporations consider alternative locations for low-cost export platforms. In this paper, we explore this important research and policy issue empirically. We focus our studies on East and Southeast Asia as well as Latin America. For Asia, we use data for eight Asian economies (Hong Kong, China, Taipei,China, Republic of Korea, Singapore, Malaysia, Philippines, Indonesia and Thailand) for 1985-2002 while for Latin America, we use data for sixteen Latin American economies (Argentina, Bolivia, Brazil, Chile, Columbia, Costa Rica, Ecuador, El Salvador, Guatemala, Mexico, Nicaragua, Panama, Paraguay, Peru, Uruguay and Venezuela) for 1990-2002. We control for the standard determinants of their inward direct investment. We then add PRC's inward foreign direct investment as an indicator of the 'PRC Effect'. Estimation of the coefficient associated with the PRC Effect proxy gives us indications about the existence of the PRC Effect. We have three results: (1) The level of PRC's foreign direct investment is positively related to the levels of inward direct investments of economies in East and Southeast Asia, while the PRC Effect is mostly insignificant for Latin American nations; (2) the level of PRC's foreign direct investment is negatively related to the direct investment of these economies as shares of total foreign direct investments in the developing countries; (3) The PRC Effect is generally not the most important determinant of the inward direct investments of these economies. Market sizes and policy variables such as openness and corporate tax rates tend to be more important.
Keywords: 330; Direktinvestition; Internationaler Wettbewerb; Ostasien; Lateinamerika; China